Guest induced reversible on–off switching of elastic frustration in a 3D spin crossover coordination polymer with room temperature hysteretic behaviour. Issue 4 (27th November 2020) - Piñeiro-López, Lucía; Valverde-Muñoz, Francisco-Javier; Trzop, Elzbieta; Muñoz, M. Carmen; Seredyuk, Maksym; Castells-Gil, Javier; da Silva, Iván; Martí-Gastaldo, Carlos; Collet, Eric; Real, José Antonio
Abstract : Reversible switch between a robust bistable two-state room temperature spin crossover (SCO) and its transformation in a four-stepped elastically frustrated SCO due to guest inclusion in a metal–organic Hofmann framework. Abstract : A binary reversible switch between low-temperature multi-step spin crossover (SCO), through the evolution of the population γ HS ( T ) with high-spin (HS)-low-spin (LS) sequence: HS1 LS0 (state 1) ↔ HS2/3 LS1/3 (state 2) ↔ HS1/2 LS1/2 (state 3) ↔ HS1/3 LS2/3 (state 4) ↔ HS0 LS1 (state 5), and complete one step hysteretic spin transition featuring 20 K wide thermal hysteresis centred at 290 K occurs in the three-dimensional (3D) Hofmann-type porous coordination polymer Fe II (3, 8phen)[Au(CN)2 ]2 · x PhNO2 (3, 8phen = 3, 8-phenanthroline, PhNO2 = nitrobenzene), made up of two identical interpenetrated pcu-type frameworks. The included PhNO2 guest ( x = 1, 1·PhNO2 ) acts as a molecular wedge between the interpenetrated 3D frameworks via PhNO2 -3, 8phen intermolecular recognition and is the source of the strong elastic frustration responsible for the multi-step regime. Detailed X-ray single crystal analysis reflects competition between spatial periodicities of structurally inequivalent HS and LS SCO centres featuring: (i) symmetry breaking (state 3) with ⋯HS–LS⋯ ordering with γ HS = 1/2; and (ii) occurrence of spatial modulation of the structure providing evidence for stabilization of local or aperiodic ordered mixed spin states for states 2 and 4 (with γ HS ≈ 2/3) and 4 (with γ HS ≈ 1/3), respectively. Below c.a. 20 K, structural and magnetic analyses show the photogeneration of a metastable HS*, state 6. The room-temperature single-step hysteretic regime appears with release of the guest ( x = 0, 1 ) and the elastic frustration, and reversibly switches back to the original four-step behaviour upon guest re-adsorption. Both uncommon relevant SCO events meeting in the same material represent a rare opportunity to compare them in the frame of antiferro- and ferro-elastic transitions.